Built Cultural Heritage Recording and Evaluation in the Traditional Settlement of Siatista in Greece: Functional and Institutional Proposals for Conservation - Eleni G. Linaki (Urban Science, 2019)
This case report explores the town of Siatista (located in the Western Macedonia Region—Greece), which is designated as a “traditional settlement”. The paper argues that, despite the relevant legislation that designated 400 settlements in Greece as “traditional settlements” and put them under protection, Siatista has no delimited traditional section. Through the years, new house typologies, demolitions, and alterations of its urban form have appeared, and Siatista has lost its identity. Having as an ultimate goal to identify proper planning guidelines and regulations for the preservation of Siatista’s built heritage, the methodology used in the paper includes the following steps: (a) recording and codification of the key legislation for the protection of Siatista, including the official urban plans (and their revisions); (b) identification and mapping of the urban form and spatial characteristics of Siatista (existing land uses, house typology, etc.); (c) identification of the alterations of the urban form and the demolitions, mainly with the use of aerial photos (1960−2014); and (d) creation of a map presenting the remaining built heritage per degree of evaluation. Following the analysis of the existing situation and the identification of the key challenges, the paper ends by defining and delimitating the well-preserved section of the town (proposing stricter rules and regulations for its preservation).